Just how much of what we taste derives from the sense of smell?. Issue 1 (December 2015) - Spence, Charles
Abstract It is frequently asserted that somewhere between 75 and 95 % of what we commonly think of as taste actually comes from the sense of smell. However, empirical evidence in support of such a precise-sounding quantitative claim is rarely, if ever, cited. Indeed, a closer look at the study that appears to have given rise to statements of this general type simply does not support the claim as made. As we will see, the often confused, and certainly confusing, use of the term "taste"—sometimes in the layman's everyday sense of flavour and, at other times, in the more precise scientific meaning of gustation, adds to the difficulty here. Furthermore, the widespread disagreement concerning which senses should be considered as constitutive of flavour perception and which merely modulatory means that it is probably not going to be possible to provide an exact answer to the question of how much of what people commonly think of as taste actually comes from the nose, until one has carefully defined one's terms. Even then, however, the answer is likely to vary quite markedly depending upon the particular combination of olfactory and gustatory stimuli that one is thinking about. Nevertheless, despite the difficulty associated with generating a precise value, or even range of values, most researchers would appear to agree that olfaction plays a "dominant" role in the tasting of food. This important observation (just without the precise-sounding percentages attached) certainly deserves to be shared more widely. Crucially, the evidence suggests that it can sometimes inspire the modernist chefs, not to mention the culinary artists and designers, to change the way in which they deliver multisensory flavour experiences to their customers (in order to capitalize on olfaction's often dominant role in our perception of food and drink).